Rancang Bangun Jig & Fixture Pemesinan Computer Numerical Control (CNC) Milling Dengan Area Kerja 300x300mm - Nur Aidi Ariyanto; Sigit Setijo Budi (Infotekmesin, 2026)
Limitations in machining accuracy and efficiency on CNC milling machines with a 300 × 300 mm working area are often caused by the use of general-purpose jig and fixture (J&F) designs that are not tailored to the characteristics of the machine and workpiece. This condition can lead to vibration, dimensional errors, and inefficient use of time and material. The research gap addressed in this study lies in the limited availability of systematic jig and fixture designs for CNC milling machines with restricted working areas. This research aims to design a jig and fixture compatible with a 300 × 300 mm CNC milling machine to improve clamping stability, machining accuracy, and process efficiency. The VDI 2222 design methodology is applied through four stages: planning, conceptualization, design, and completion, supported by Computer-Aided Design (CAD). Two design alternatives are evaluated, and the optimal concept is selected based on clamping stability criteria. The results are a final jig and fixture design and detailed engineering drawings ready for prototype fabrication, suitable for small-scale CNC milling machines.